Cerebello-Cerebral Network Dynamic of Basketball Athletes in Motor Control Tasks. - QI, YAPENG; WANG, YIHAN; FANG, WENXUAN; LI, XINWEI; DU, XIAOXIA (Medicine & Science in Sports & Exercise, 2026)
Purpose: The cerebellum is essential for motor control due to its dynamic interactions with the sensorimotor network (SMN). Within the cerebellum, motor functions are organized into two distinct representations, known as the first motor representation (MRP1) and the second motor representation (MRP2). While long-term training in athletes optimizes motor control, the functional reorganization in the cerebellum and its interaction with the SMN remains unclear. Specifically, the unique contributions of MRP1 and MRP2 to motor expertise remain poorly understood. Methods: We utilized task-based functional magnetic resonance imaging and dynamic causal modeling to compare 55 elite basketball athletes with 65 nonathlete controls during two general motor tasks: a grip force task focused on upper-limb control and a leg raise task assessing lower-limb postural control. We examined brain activation and effective connectivity across cerebellar and cortical motor regions. Results: No significant differences in regional brain activation were found between the groups. Dynamic causal modeling analysis revealed that, compared with nonathletes, athletes' MRP1 showed a significant stronger bidirectional connectivity with effector regions in both tasks. In contrast, athletes' MRP2 exhibited a significant decreased connectivity with effector regions during the leg raise task. Additionally, there was a nonsignificant trend toward increased connectivity from MRP2 to the motor planning regions of SMN in athletes. Conclusions: Our findings suggest that the neural signature of expert motor control is better reflected by refined interactions within the cerebello-cerebral circuit, rather than by heightened neural activation. Athletes demonstrate a reorganization of cerebellar modulation, with MRP1 facilitating automatic motor output and MRP2 showing reduced involvement during complex tasks. These results provide new insights into the neural basis of motor expertise and could inform targeted approaches in sports training and neurorehabilitation.